A preliminary study on the effect of enriching feed with fish oil on the growth and survival rate of climbing perch Anabas testudineus - Desiana Trisnawati Tobigo; Samliok Ndobe; Adriansyah Adriansyah (Aceh Journal of Animal Science, 2021)
The climbing perch (Anabas testudineus) is an economically valuable freshwater fish. Relatively slow growth has been a challenge in the domestication of this species in Indonesia. Nutrition, including feed lipid content, is one factor affecting growth. This study examined the effect of enriching feed with fish oil on the growth and survival of climbing perch (A. testudineus) fingerlings. The research was carried out at the Water Quality and Aquatic Biology Laboratory, Faculty of Animal Husbandry and Fisheries, Tadulako University, Palu, Central Sulawesi, Indonesia from 17 December to 18 January 2020. A completely randomized design (CRD) was used with 4 treatments and 5 replicates. The fish oil feed enrichment treatments were: A (control, 0%); B (1%); C (2%) and D (3%). Water quality remained within the optimum range throughout the research period. Over the month, climbing perch absolute weight gain ranged from 2.4±0.981 g (A) to 3.4 ± 0.836 g (D), while growth in length ranged from 0.404±0.092 cm (A) to 0.504±0.071 cm (D); however, the differences were not statistically significant (P0.05). The survival rate of climbing perch over the one month study period was 100% under all treatments, indicating that basic nutritional needs were met. Enrichment of a commercial feed with fish oil (Scott’s emulsion) at rates of 1-3% did not provide a significant benefit in terns of climbing perch fingerling growth.